PEMANFAATAN WAFER LEGUMINOSA SEBAGAI PAKAN ALTERNATIF TERNAK KAMBING DI DAERAH LAHAN KERING - Agustinus Paga; Bernadete B. Koten; Theresia N.I. Koni (Partner, 2008)
Use of Wafer Legume as Goats Feeds Alternative in Semi Arid Area. The experiment was conducted at Goats house Laboratory of Production and Reproduction, Kupang State Agriculture Polytechnic, from Mei to July 2006. This research aimed to know the advantage of wafer legume used for goat’s feed, especially feed intake, digestion, body weigh gain, rumen concentration of NH3 and VFA. The experiment used completely randomized design. Nine goats were randomly divided into 3 groups to receive three treatments. The treatments were R0 (kume grass hay), R1( R0 + wafer -1 of 1,5% body weight gain, R2 ( R0 + wafer-2 of 1,5% body weight gain. Parameters measured were nutrient intake, nutrient digestion, body weight gain, rumen concentration of NH3 and VFA. The data was analysed by using Analysis of Variance (ANOVA) and Duncan Multiple Range Test (DMRT). The result indicated that wafer legume did not significantly affected to organic matter intake and body weight gain, while the significant effect was found in digestion, rumen concentration of NH3 and VFA. It Could be concluded that wafer legume improve digestion, rumen concentration of NH3 and VFA of goats. Keywords: Wafer, Legume, Goats, Body weight gain